(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2024)
The pharmaceutical industry is mostly dedicated to the production of drugs in solid forms such as tablets and capsules with active ingredients and excipients in the same physical state. Regarding the regulatory requirements for the analytical development and implementation of solid-state analyses, internationally recognized pharmaceutical compendia play an important role. However, the information contained in the various general chapters and monographs differs from each other, especially in countries that have national pharmacopeias, such as Brazil. Thus, the main objective of this work is to critically evaluate, based on the technical-scientific literature, the harmonization of the United States, European, British, Japanese and Brazilian pharmacopeias with respect to the following analytical techniques used for solid-state characterization: X-ray powder diffraction, differential scanning calorimetry, thermogravimetric analysis, and infrared and Raman spectroscopies. The working principle of each analytical technique, as well as the methodological parameters that impact the implementation of the analyses, are detailed. The results indicate that, in terms of solid-state characterization analysis, the adoption of unified scientific standards and principles is not yet a reality for all compendia. Additionally, the lack of harmonization between BrazP and the other compendia is especially significant, considering that ANVISA is an ICH member, the main entity responsible for promoting harmonization.